Statistical Profiling of the Unemployed - Grundy, John (Studies in Political Economy, 2015)
Labour market policy in Canada has undergone profound reforms over the past several decades. Successive federal and provincial governments have sought to “activate” the unemployed through measures such as Employment Insurance (EI) retrenchment and employment service models that stress individual responsibility for the problem of unemployment. This paper analyzes a little known attempt by federal officials to implement statistical profiling of the unemployed in employment service delivery during the mid-1990s. Known as the Service Outcome Measurement System (SOMS) and intended for use by frontline employment counsellors, the technology computed personal data about unemployed service users to predict the employment outcomes of different service options.
Keywords: data; employment services; neoliberalism; public administration; unemployment